Braveheart - Wallace, Randall; Ladd, Alan, 1937-; Davey, Bruce; Gibson, Mel; Marceau, Sophie, 1966-; McGoohan, Patrick, 1928-2009; McCormack, Catherine; Paramount Pictures Corporation; Icon Productions; Ladd Company; Pioneer Entertainment (USA) ([S.l.] : Pioneer Entertainment : Paramount, 1996)
William Wallace is a bold Scotsman who used the steel of his blade and the fire of his intellect to rally his countrymen to liberation
Originally released as a motion picture in 1995
Director of photography, John Toll ; editor, Steven Rosenblum ; music, James Horner
Mel Gibson, Sophie Marceau, Patrick McGoohan, Catherine McCormack
MPAA rating: R
Laser Disc, CLV, widescreen, THX, surround sound, stereo
Closed-captioned for the hearing impaired
Keywords: Wallace, William, -- Sir, -- d. 1305 -- Drama; Scotland -- History -- Wallace's Rising, 1297-1304 -- Drama; Historical films; Biographical films; Feature films; Films for the hearing impaired